2008
DOI: 10.1093/ijtj/ijn039
|View full text |Cite
|
Sign up to set email alerts
|

Testifying in an International War Crimes Tribunal: The Experience of Witnesses in the Special Court for Sierra Leone

Abstract: The research described in this article investigates the extent to which witnesses who testified in the Special Court for Sierra Leone (SCSL) report the experience as positive or negative. It also seeks to identify the factors that contribute to these evaluations. It reports the results of structured interviews conducted with 171 witnesses who testified in the SCSL. The finding that emerges most strongly is that the experience of testifying was positive for the majority of witnesses. The courtroom environment w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…A number of findings on the experience of testifying in a war crimes tribunal have been drawn from an internal program evaluation at the SCSL (Charters, Horn, & Vahidy, 2008). In one pertinent article (Horn, Charters, & Vahidy, 2009a), witnesses reported that they experienced the courtroom environment as supportive and rated their experiences of both examination-in-chief and cross-examination as being largely positive. Only two variables—worry at the time of testimony and respect from court staff—predicted witnesses’ evaluation of their experience.…”
Section: International War Crimes Courtsmentioning
confidence: 99%
“…A number of findings on the experience of testifying in a war crimes tribunal have been drawn from an internal program evaluation at the SCSL (Charters, Horn, & Vahidy, 2008). In one pertinent article (Horn, Charters, & Vahidy, 2009a), witnesses reported that they experienced the courtroom environment as supportive and rated their experiences of both examination-in-chief and cross-examination as being largely positive. Only two variables—worry at the time of testimony and respect from court staff—predicted witnesses’ evaluation of their experience.…”
Section: International War Crimes Courtsmentioning
confidence: 99%
“…The more motivated witnesses are to testify, the more of a vested interest they have in the outcome of the experience (Stepakoff et al 2014;Henry 2011). Witnesses may feel like they are contributing to justice, preventing future wars, setting the historical record straight, honoring loved ones, and putting the past behind them (Stepakoff et al 2014;Cody et al 2014;Stover 2005;Hodžić 2010;Horn, Charters, and Vahidy 2009b). We suggest that witnesses who are highly motivated and those who feel they have contributed to justice will perceive testifying as a more positive experience.…”
Section: Wartime Experiences and Testimonial Processmentioning
confidence: 90%
“…Truth-telling via truth commissions may bring emotional relief in post-conflict societies (Gibson 2006;Brounéus 2010), but more formal war crimes tribunals may provide greater fulfillment for survivors because the trials may better address victims' needs and may be more effective for achieving justice (Mendeloff 2009; Barria and Roper 2005). Indeed, different studies echo this latter proposition at the ICC (Cody et al 2014) and the Special Court for Sierra Leone (Horn, Charters, and Vahidy 2009b, Stepakoff et al 2014, 2015b. Witness motivation is most commonly related to being able to tell their story, to contribute to justice, to rebuild the post-conflict society, to find out what happened to loved ones, to tell the truth about the historical record and the crimes committed, and to prevent others from being harmed (Stepakoff et al 2014;Stover 2005).…”
Section: Witness Impact and Resiliencementioning
confidence: 99%
“…The dilemmas that victims face with respect to justice, in particular when they are disinclined to pursue legal justice because of a lack of trust and limited information as to procedures and consequences, have been highlighted (Hamber, 2009; Kordon et al, 2010). Other studies have shown that, under the right conditions, witnesses, at least in international courts, experienced some form of relief in feeling that the courts had acknowledged their suffering (Horn, Charters, & Vahidy, 2009) and helped them discharge their moral duty to testify on behalf of the dead (Stover, 2005). However, Stover (2005) also points to the hardships involved in being witnesses in such trials.…”
Section: Studies On Transitional Justice and Victims’ Needsmentioning
confidence: 99%
“…Standing witness in court and observing that those responsible have been detained may be experienced as a personal triumph (Edelman, 2010). Finally, the importance of support to the witnesses when they present evidence in court has been underscored (Horn et al, 2009; Lagos, 2010).…”
Section: Studies On Transitional Justice and Victims’ Needsmentioning
confidence: 99%